PERSEPSI WISATAWAN TERHADAP VARIASI WISATA DI PANTAI GLAGAH KULONPROGO - , DESITA ANGGRAENI; , Dr. M Baiquni M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Glagah beach is one of leading tourist attraction in Kulonprogo regency. Variety of tours offered become point of interest for tourist. Perception analysis is a way to know visitors opinion about the exixtence of tourist attraction. The purposes of this research are: (1) To describe visitors opinion toward tourism variation at Glagah beach, Kulonprogo regency.